2013
DOI: 10.5012/bkcs.2013.34.6.1814
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on Interactions between N-Butylpyridinium Nitrate and Thiophenic Compounds

Abstract: − and NAP are weak in terms of structural properties and NBO, AIM analyses. DBT is prior to adsorption on N-butylpyridinium nitrate ionic liquid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…However, the selectivity for metal‐based ionic liquids is very complicated. The extractive mechanisms were mainly ascribed to hydrogen bond and π‐π interactions as well as CH‐π interactions . Similar order can be found in Figure b (electron affinity) and Figure e (electrophilicity).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, the selectivity for metal‐based ionic liquids is very complicated. The extractive mechanisms were mainly ascribed to hydrogen bond and π‐π interactions as well as CH‐π interactions . Similar order can be found in Figure b (electron affinity) and Figure e (electrophilicity).…”
Section: Discussionsupporting
confidence: 70%
“…In ADS system, the removal mechanism is suggested to be the π‐π interaction between sulfides and sorbents . While in EDS system, the mechanisms were mainly ascribed to hydrogen bond and π‐π interactions as well as CH‐π interactions . Both of the mechanisms are not related to the electron densities of sulfur atoms.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, previous works have shown that the strongest interaction often occurs on the opposite site of the sulfur atom, like complex-X-c or complex-X-d (X = TH, BT, and DBT). 23,28,59,60 Moreover, the strongest interaction is −1.0 kcal/mol lower than the interaction in the BT system. It is clearly shown that sulfur compounds with multirings improve the interaction energy in the EDS by [BMIM] + [AlCl 4 ] − IL.…”
Section: → +mentioning
confidence: 94%
“…To date, there were many theoretical works focused on non-metal-based ILs. The extractive mechanisms were mainly ascribed to hydrogen bond and π–π interactions as well as CH−π interactions . For metal-based ILs, Fe-containing ILs have been studied by density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%